Development of an integrated library system for Ramon Magsaysay (Cubao) High School Library - Baylas, Bianca Rei T.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
RMCHS is aiming to enhance computer literacy and enable them to cope with changes brought about by modernization and industrialization. However, without a system, there will be no way to effectively and efficiently utilize the services of the library to realize their goals. And by developing a system, there'll be a way to understand problems and discover opportunities in the area of technology.
The study identified areas and services to be improved and/or automated by conducting a survey with structured questionnaire. The questionnaire used a 5-point scale system to determine the importance of features and modules to patrons and librarians. Modules and features with a rate of 2.5 or higher were included in the system. The sample size was determined using Krejcie and Morgan's proportional allocation formula. In developing the system, Systems Development Life Cycle was followed. However, due to time constraint, evaluation and maintenance phase was not included.
Based on the survey conducted, the design focused on three important modules of an integrated library system: cataloging, circulation, and the OPAC. The final system was developed using free and open source software packages to cut cost. Although it was developed in a Linux platform, the system can run on any computer as long as it has a web browser, as it is platform independent. The web interface is managed using Joomla, a content management system. Apache was used as web server and MySQL as database. PhpMyAdmin was also used to easily manage MySQL databases. The library system modules were from Polerio Babao III's PhpMyLibrary. It consists of cataloging, circulation and OPAC modules and strictly follows USMARC standard, the official Machine Readable Cataloging (MARC) format for digital catalogs and libraries, for adding materials. "
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Integrated library systems (Computer systems).